(untitled) (Journal of the College of Basic Education, 2023)
Physical fitness has become of great importance in the field of scientific progress, which opens dayA day later, new horizons for its development, as it constitutes a cornerstone in achieving the health aspectsper capita in general, and thus it is considered a measure of the extent of progress of countries and societies.There is no doubt that physical fitness is a measure by which we can predict the extent of progress.achieved by the curricula in the faculties and departments of physical education in particular, as a basis forIt can be dispensed with in games, events and all sporting activities, and this is confirmed byMarwan Abdel Majeed Ibrahim, where he says ((that physical fitness is the backbone and the base on whichNo discussion is accepted about its importance because it has become one of the basic postulates in education.Sports)), (1) and in this we see the importance of physical fitness, as it helps students in performance and proficiencyAnd the skillful completion of all practical lessons as the basic rule for them.On the other hand, it works on the development of other voluntary qualities that are necessaryFor the individual in general and for the students of the faculties of physical education, as it helps them to continue and develop inAll practical materials and skills.